2002
DOI: 10.1111/j.1939-1668.2002.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Creativity Defined: Implicit Theories in the Professions of Interior Design, Architecture, Landscape Architecture, and Engineering

Abstract: The purpose of this study was to examine implicit theories of creativity in related fields through a mail survey of 3 1 3 professors randomly selected from accredited programs in interior design, architecture, landscape architecture, and engineering. To describe a highly creative practitioner in their respective fields, the respondents completed the Gough Adjective Check List (ACL), scored with the Domino creativity scale (Cr). The interior design professors generated a profile of the creative practitioner tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…A creative person is sometimes defined as an individual who has “the capacity to produce new or original ideas” (Goldschmidt & Tatsa, 2005, p. 593). Portillo (2002) surveyed professors in interior design, architecture, landscape architecture, and engineering to examine perceptions of creativity. While over half of her sample described creative practitioners as original she found that “the interior design profile differed from the other three groups by being more frequently cited as … original” (p. 20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A creative person is sometimes defined as an individual who has “the capacity to produce new or original ideas” (Goldschmidt & Tatsa, 2005, p. 593). Portillo (2002) surveyed professors in interior design, architecture, landscape architecture, and engineering to examine perceptions of creativity. While over half of her sample described creative practitioners as original she found that “the interior design profile differed from the other three groups by being more frequently cited as … original” (p. 20).…”
Section: Resultsmentioning
confidence: 99%
“…The creative person empirical referents were as follows: Personality attributes including creative attitude were studied by Dohr (1982) and Portillo (2002) using Gough's Adjective Checklist with Domino's (1970) creativity scale. Perceived creativity levels were measured by Gardner and Weber (1990) using the instrument “How Do You Think?” (Davis, 1977).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality is an important concept in psychology, which may be identified as particular combination of the individual's emotional, behavioural and attitudinal pattern in different situations (Sandhu & Kapoor, 2013). Portillo (2002) conducted an exploratory study to compare the Personality of interior designers, architects, landscape architects, and engineers. Results indicated that each group was described with specific Personality traits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One growing area of research is the study of creativity in different fields in order to help understand how members of a profession define themselves in their field. An example of this kind of variance can be found in the research by Portillo who surveyed 313 professors from four related fields: interior design, architecture, landscape architecture, and engineering [5].…”
Section: Introductionmentioning
confidence: 99%